1998
DOI: 10.1080/02571862.1998.10635130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tied ridges on grain yield response of Maize (Zea mays L.) to application of crop residue and residual N and P on two soil types at Alemaya, Ethiopia

Abstract: Field experiments were conducted on two soil types over a period of five years (1986)(1987)(1988)(1989)(1990) to investigate the effects of tied ridges and planting systems on the grain yield response of maize to applications of crop residue and residual Nand P fertilizers. Grain yields were increased by the use of tied ridges. Further increases in grain yields resulted from residual Nand P and crop residue applied separately or together. Under all fertilization practices, planting in the furrow of tied ridges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 11 publications
(11 reference statements)
2
9
0
Order By: Relevance
“…Rainfall was often stormy and in season two for example, 75% of the seasonal rainfall was received only in 7 days. Tied-ridge systems have been observed to increase yield over conventional tillage by up to 85% (Nyakatawa et al 1996) but the increase depends on soil type, ridge flow (closed or open) and planting position (in furrow or ridge topas in our case Belay et al 1998). Negative yields under tied ridges have also been reported and were attributed to high rainfall ([700 mm Jensen et al 2003) and water logging (Olufayo et al 1994).…”
Section: Discussionsupporting
confidence: 46%
“…Rainfall was often stormy and in season two for example, 75% of the seasonal rainfall was received only in 7 days. Tied-ridge systems have been observed to increase yield over conventional tillage by up to 85% (Nyakatawa et al 1996) but the increase depends on soil type, ridge flow (closed or open) and planting position (in furrow or ridge topas in our case Belay et al 1998). Negative yields under tied ridges have also been reported and were attributed to high rainfall ([700 mm Jensen et al 2003) and water logging (Olufayo et al 1994).…”
Section: Discussionsupporting
confidence: 46%
“…Under MD, optimum yields are obtained under temperature increases of +1.0 • C and changes in precipitation of +30%. Thus, in cases of high temporal rainfall variability, as in our case study site, it is advised that farmers adopt infield rainwater harvesting, such as tied ridges [25,44,45,[53][54][55], since they prolonging soil moisture. Although alternatives like providing irrigation may be effective, not only do these require further investigation regarding cost-benefit advantages, but these also may come with insurmountably high initial investment costs [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found yield discrepancies even at the within-field scale, as some parts of the field may produce more of a crop relative to the rest of the field, indicating microscale interactions between climate, soil, topography, and management [21]. Generally, soils with higher content of swelling clay and silt better retain and release soil moisture; therefore, under adverse limited rainfall conditions, these properties provide a buffer to crop production [37]. Previous studies suggest that the effect of tied ridges is much more pronounced under limited rainfall in high clay content soils than in sandy soils [37].…”
Section: Discussionmentioning
confidence: 99%